Investments in Soft Skill Training in Unimas: A Human Capital Development Approach - Shafinah, Rahim (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Graduate development has been a key area of focus for all public universities in Malaysia since its introduction by the Ministry of Higher Learning in 2006. The concern for graduate employability recently makes the need to prepare fresh graduates with the right and sufficient social skills even pressing. The current research is exploratory in nature and an effort to weigh the cost effectiveness of the decade long investment in soft skill training by UNIMAS. To meet this objective, feedbacks from three groups of stakeholders including students, facilitators and employers were collected via surveys and interviews. Data on costs related to provision of soft skill training to first year students were retrieved from internal database. Findings show that while responses with regards to the benefits are mixed in terms of its effects, there are ways to improve the cost efficiency of the investment. Also the subjective measure of effectiveness of the delivery and assessment of the soft skill course can be enhanced by standardizing certain elements of the modules. However, given the unique nature to social skills amongst students, it requires a delicate approach combined with strong will and commitment of the management. The researcher suggests all universities to treat the offering of the soft skill course as earnestly as any other core courses at their respective faculties.